2016
DOI: 10.1016/j.appet.2016.08.104
|View full text |Cite
|
Sign up to set email alerts
|

Association between objective and subjective binge eating and psychopathology during a psychological treatment trial for bulimic symptoms

Abstract: Although loss of control while eating (LOC) is a core construct of bulimia nervosa (BN), questions remain regarding its validity and prognostic significance independent of overeating. We examined trajectories of objective and subjective binge eating (OBE and SBE, respectively; i.e., LOC eating episodes involving an objectively or subjectively large amount of food) among adults participating in psychological treatments for BN-spectrum disorders (n=80). We also explored whether changes in the frequency of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…One study found higher baseline SBE frequency to be predictive of non‐remission from an eating disorder , while another found OBE, but not SBE, to predict remission status . Finally, while two studies reported that individuals with OBE and SBE generally did not differ from one another or from controls with no LOC eating in terms of changes in eating‐related and general psychopathology , another found that changes in SBE, but not OBE, predicted changes in eating‐related and general psychopathology during and after psychological treatment .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One study found higher baseline SBE frequency to be predictive of non‐remission from an eating disorder , while another found OBE, but not SBE, to predict remission status . Finally, while two studies reported that individuals with OBE and SBE generally did not differ from one another or from controls with no LOC eating in terms of changes in eating‐related and general psychopathology , another found that changes in SBE, but not OBE, predicted changes in eating‐related and general psychopathology during and after psychological treatment .…”
Section: Resultsmentioning
confidence: 98%
“…Ultimately, developing and implementing efficacious interventions for binge eating‐related problems across the size and LOC‐severity spectrum should be a priority. Research has shown that SBE may be less responsive than OBE to psychological treatments addressing behavioural and affective antecedents , suggesting that there may be unique triggers of LOC in the absence of overeating that aren't adequately addressed in current interventions. Treatments focused on improving distorted cognitions about one's eating behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two main outcomes were considered in the current study based on previous studies showing the importance of baseline bingeing frequency as an indicator of general psychopathology and treatment outcome (Goldschmidt et al, ; Peterson et al, ) and on an established methodology for the analysis of outcomes in psychotherapeutic treatments (Jacobson & Truax, ). First, the level of improvement was defined as the percentage of reduction in BPW between the baseline assessment and the end of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Both comorbid depression or anxiety and the use of selective serotonin reuptake inhibitors (SSRIs) may influence changes in both CT 26, 27 and BN symptoms 28, 29 over time. Thus, growth curve and multilevel models were conducted with these additional time-varying covariates (i.e., comorbid depression or anxiety and current SSRI use) at each time point.…”
Section: Methodsmentioning
confidence: 99%